2020
DOI: 10.5688/ajpe7232
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Curricular Integration Between Patient Care Laboratory and Introductory Pharmacy Practice Experience on Documentation

Abstract: Objective. To assess the impact of curricular changes made through vertical integration between Patient Care Laboratory and Introductory Pharmacy Practice Experience (IPPE) courses on documentation outcomes. Methods. Curricular changes to address student pharmacist documentation deficiencies were developed by laboratory and experiential faculty members. A documentation activity using subjective, objective, assessment, plan (SOAP) notes completed in one IPPE rotation block, pre-intervention, were graded and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…[1,4,6,15,26,27] These are mainly popular worldwide as communication tools to facilitate the PCP, pharmacotherapy recommendations, and progress reports on health outcomes. [2,5,18,29–31]…”
Section: Discussionmentioning
confidence: 99%
“…[1,4,6,15,26,27] These are mainly popular worldwide as communication tools to facilitate the PCP, pharmacotherapy recommendations, and progress reports on health outcomes. [2,5,18,29–31]…”
Section: Discussionmentioning
confidence: 99%
“…Clinical notes were scored using a modified, 25-point checklist based on the American Pharmacist's Association guidelines and adopted from others. 27,35 This modified checklist only evaluated the presence or absence of material in each section, not on relevancy since this required more clinical expertise.…”
Section: Methodsmentioning
confidence: 99%
“…While this research has shown improvements, there is limited data on the use of explicit instruction in teaching clinical note writing. 27 The purpose of this study is to investigate the role of worked examples or problem-solving practice in the learning and reinforcement of writing a clinical note. Specifically, we will test the worked example-problem-solving (WEPS) paradigm against the worked example-worked example (WEWE) paradigm in writing clinical notes.…”
Section: A J P Ementioning
confidence: 99%
“…Previous studies support the use of simulated electronic health records (EHRs) as a tool to aid in application-based learning (Vyas, Bray, & Wilson, 2013). A study conducted at the University of Kentucky College of Pharmacy documented a significant improvement in student documentation and writing skills through Subjective, Objective, Assessment, Plan (SOAP) notes after the implementation of an EHR platform into a Patient Care Laboratory course (Divine, Jones, & Gokun, 2020). Another qualitative review conducted at Midwestern University, Chicago College of Pharmacy, utilised simulation-based learning to teach cardiovascular topics (Kolanczyk, Borchert, & Lempicki, 2019).…”
Section: Introductionmentioning
confidence: 99%